Modeling of dimmable High Power LED illumination distribution using ANFIS on the isolated area - ORAL, BÜLENT; KIYAK, İSMAİL; TOPUZ, VEDAT (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
High power light emitting diodes (HP-LEDs) are more suitable for energy saving applications and have becoming replacing traditional fluorescent and incandescent bulbs for its energy efficient. Therefore. HP-LED lighting has been regarded in the next-generation lighting. In this study, illumination distribution of white color HP-LED is modeled by adaptive neuro-fuzzy inference system (ANFIS) approach on the isolated area while LED head is fixed. Subtractive clustering with hybrid learning approach is used to train the realized ANFIS architectures. End of the numerous experiment we finally concluded that, ANFIS could be used to modeling the illumination distribution applications perfectly. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: High Power LED; ANFIS; Illumination distribution; SYSTEM DYNAMICS MODEL